Nippon Paint’s Mosque-Musala CSR Program on Paint Sales Impact: A Case Study - Topan Wijaksono (Institut Komunikasi dan Bisnis LSPR, 2025)
Corporate Social Responsibility (CSR) has become one of the key strategies in managing the relationship between companies and society. However, in practice, CSR is generally utilized only as a means of building corporate image, and it is rarely employed as part of a marketing strategy aimed at boosting product sales. This study seeks to analyze the influence of CSR programs on increasing product sales, using a case study of Nippon Paint Indonesia’s CSR program implemented in Banten during February–March 2024. The program engaged 35 mosques and prayer halls as well as 17 building material stores, with research focusing on BA Bangunan Group, which consists of 12 stores and 22 houses of worship. Beyond the conceptual importance of a CSR program itself, the appropriate publication and dissemination of such initiatives can also raise consumer awareness and attract purchasing behavior. In this case, Nippon Paint Indonesia strategically utilized digital marketing to publicize its CSR activities in ways that captured consumer attention and encouraged purchases. This research applied a descriptive quantitative approach with comparative methods, analyzing sales data both before and during the CSR program, measuring sell-in (from Nippon Paint to stores) and sell-out (from stores to end consumers). The findings are expected to provide new insights that CSR can not only be used as a corporate social obligation or public relations activity but also as an effective marketing strategy that contributes directly to sales growth in Indonesia.